Gastroprotective Effect of Ethanol Stem Bark Extract of Pepolo (Bischofia javanica Blume) Against Aspirin-Induced in Wistar Rat - Yuliet Susanto; Rini Saputri; Khildah Khaerati (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Prolonged use of nonsteroidal anti-inflammatory drugs (NSAIDs) can trigger ulcers and bleed in the gastric mucosa. Pepolo stem bark (Bischofia javanica Blume) was a traditional plant that has been empirically used to treat gastric ulcers. This plant contains secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and triterpenoids with gastroprotective potential. This study aims to determine the gastroprotective effect of pepolo stem bark extract (PSBE) against gastric ulcers of Wistar rat induced by Aspirin. The study used 24 rats grouped into six groups. Aspirin (150 mg/kg BW) was administered orally to all the groups except normal control. After 4 h of induction, normal and negative control received Na CMC 0.5%, while the positive group received Omeprazole (3.6 mg/kg BW). The remaining low, middle, and high dose groups received PSBE (100, 200, and 300 mg/kg BW). The treatment was given orally for eight days. On the 9th day, the rats were dissected and tested on the stomach organs. The parameters measured were scores based on the severity of rat peptic ulcers, ulceration index, and percentage protection ratio. The scoring data were analyzed using the Kruskal-Wallis non-parametric test and post hoc the Mann-Whitney test. The administration of PSBE showed the ability to reduce the ulcer index and increase the percentage of ulcer inhibition significantly compared to the negative control (p<0.05). This study showed that PSBE could be a promising gastroprotective herbal medicine.Key words: Aspirin, pepolo stem bark, gastric ulcer